REVIEW PAPERSChlamydia trachomatis – characteristics and diagnostics of infections - Gornowicz, Justyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Chlamydia are bacteria which cause several diseases, including ones with lethal course. Chlamydia trachomatis is the most common sexually transmitted bacteria worldwide. Screening for chlamydial infection might reduce the incidence of complications of disease. Molecular methods of pathogen detection such as polymerase chain reaction (PCR) and ligase chain reaction (LCR) are making increasing progress in diagnostic laboratories. Nucleic acid amplification techniques (NAAT) allow better identification of the pathogen and provide a simple, sensitive, rapid and reliable means for detection of the organism. This fact makes these methods a very convenient tool. In this article the biology and systematics of Ch. trachomatis and diagnostic methods, including culture methods and non-culture methods for detection of Ch. trachomatis, are presented.